Psychosocial characteristics of blood donors influence their voluntary nonmedical lapse. Issue 11 (7th November 2018) - Merz, Eva‐Maria; Ferguson, Eamonn; van Dongen, Anne
Abstract : BACKGROUND: Approximately 10% of Dutch donors lapse yearly. Common reasons are nonvoluntary medical issues (e.g., low hemoglobin), reaching the upper age limit, and voluntary (e.g., own request, nonresponse). Little is known about predictors of voluntary noncompliance (lapses). Psychosocial characteristics have been linked to various health behaviors, including voluntary noncompliance. Hence, we investigated whether psychosocial characteristics, measured before the first donation, similarly predict subsequent voluntary nonmedical lapse. STUDY DESIGN AND METHODS: New donors (n = 4861) randomly received a blood donation survey between July 2008 and March 2009, before their first appointment at the blood bank. Voluntary lapses included personal reasons, nonresponse to invitations, donor who could not be reached, and no show. Univariate and multivariate Cox regression models of lapse on psychosocial characteristics and confounders (e.g., demographics) were estimated. RESULTS: Of 2964 donors who took the questionnaire, more than one‐third (36.5%) had voluntarily lapsed due to nonmedical reasons by 2016. Univariate regression showed that lapse negatively associated with norms, attitudes, and intentions toward blood donation; self‐efficacy; and more donation experience. Lapse positively associated with anxiety. Multivariate Cox models showed that lapse was primarily driven by anxiety and need for information. CONCLUSION: Certain psychosocial characteristics increase risks of voluntary lapse. Especially donors with higher donation anxiety had increased lapsing risks. They might benefit from extra attention during donation. Donors with more information need or wish about procedure and patients were less likely to lapse, indicating that binding with the blood bank might prevent lapse. Generally, this study showed that donor lapse and donor return are determined by different psychosocial factors not just the reverse of each other.